ChemInform Abstract: The Equiatomic Intermetallics REPtCd (RE: La, Ce, Pr, Nd, Eu) and Magnetic Properties of CeAuCd. Issue 27 (18th June 2015) - Johnscher, Michael; Tappe, Frank; Niehaus, Oliver; Poettgen, Rainer
Abstract The title compounds are prepared by induction‐melting of the elements in sealed Nb ampules (1323 K for 3 h and 773 K for 4 d) and characterized by powder XRD.